VARIETAL RESPONSES OF SOYBEAN (GLYCINE MAX L. MERRILL) TO GROWTH, YIELD AND NODULATION IN THE SUDAN SAVANNA ECOLOGICAL ZONE OF NIGERIA. (Wudil Journal of Science and Technology Education, 2025)
Field trials were conducted at Aliko Dangote University of Science and Technology, WudilTeaching and Research Farm, Gaya, Kano State (Latitude: 11.9331° N, Longitude: 8.5216° E),to study the growth, yield and Nodulation of some soybean varieties in Sudan Savannah Agro-ecological zone of Nigeria. The treatments consisted of nine soybean varieties (TGX 1448-2E,1987-10E, 1740-1F, 1987-62F, 1904-6F, 1951-3F, 1945-1F, 1835-10E, 1955-4F). These werelaid out in a randomized complete block design and replicated fourtimes. Data collected includedCanopy Height, Number of Branches, Canopy Spread, Nodulation, Number of Pods per Plant,Number of Seeds per Pod, 100 Seeds Weight, Haulm fresh weight, Haulm Dry Weight and GrainYield per hectare. The data were analyzed using Analysis of Variance and means separated byDuncan Multiple Range Test (DMRT) at 5% level of probability using GenStat statisticalpackage. The result of the investigation revealed that variety significantly affected growth, yieldand nodulation characters studied. The greatest yield per hectare was produced by TGX 1740-1Fand TGX 1904-6F which were statistically similar. While the least was obtained by TGX 1945-1F. In conclusion, two soybean varieties TGX 1740-1F and TGX 1904-6F were identified forgreater grain and Stover yield at Gaya.
Keywords: Varieties; Growth, Yield, Varieties, Soybean.